PENGARUH KUALITAS PELAYANAN TERHADAP KEBERHASILAN SISTEM ELEKTRONIK MANAJEMEN HUBUNGAN PENGGUNA: PERAN MEDIASI KEPUASAN PUBLIK PADA OPD KABUPATEN WAKATOBI - Juhardin A; La Hatani; Sinarwaty Sinarwaty (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this research is to examine and explain the effect of service quality on the success of the e-MHP system through the mediating role of public satisfaction in the OPD of Wakatobi Regency. The study design is based on a quantitative approach with a cross-sectional survey data collection method. Data collection is done online using an instrument in the form of a questionnaire via the https://docs.google.com/forms/dz page. The population of this study were all employees of the OPD of Wakatobi Regency as many as 40 people who served as operators of the electronic service system. The analytical tool used in testing the hypothesis is Partial Least Square (PLS).The results showed that service quality had a positive and significant effect on public satisfaction and the success of the e-MHP system. Then public satisfaction has a positive and significant effect on the success of the e-MHP system. Finally, the results of the study prove that public satisfaction acts as a partial mediation of the effect of service quality on the success of the e-MHP system. This means that the increasing implementation of service quality can make a significant contribution to increasing public satisfaction and the success of the e-MHP system. Finally, good service quality can also make a significant contribution to increasing the success of the e-MHP system at the Wakatobi District OPD either directly or through the mediating role of public satisfaction